Biomechanics in the onset and severity of spondyloarthritis: a force to be reckoned with - Mark Hwang; Priyanka Iyer; Lauren Ridley; Michael M Weisman (RMD Open)
Increasing evidence suggests that there is a pivotal role for physical force (mechanotransduction) in the initiation and/or the perpetuation of spondyloarthritis; the review contained herein examines that evidence. Furthermore, we know that damage and inflammation can limit spinal mobility, but is there a cycle created by altered spinal mobility leading to additional damage and inflammation?Over the past several years, mechanotransduction, the mechanism by which mechanical perturbation influences gene expression and cellular behaviour, has recently gained popularity because of emerging data from both animal models and human studies of the pathogenesis of ankylosing spondylitis (AS). In this review, we provide evidence towards an appreciation of the unsolved paradigm of how biomechanical forces may play a role in the initiation and propagation of AS.